Resurgent Toba—field, chronologic, and model constraints on time scales and mechanisms of resurgence at large calderas - de Silva, Shanaka L.; Mucek, Adonara E.; Gregg, Patricia M.; Pratomo, Indyo (Frontiers in Earth Science, 2015)
New data reveal details of the post-caldera history at the Earth’s youngest resurgent supervolcano, Toba caldera in Sumatra. Resurgence after the caldera-forming 74 ka Youngest Toba Tuff eruption uplifted the caldera floor as a resurgent dome, Samosir Island, capped with 100m of lake sediments. 14C age data from the uppermost datable sediments reveal that Samosir Island was submerged beneath lake level ( 900m a.s.l) 33.7 ky. Since then, Samosir experienced 700m of uplift as a tilted block dipping to the west. Using 14C ages and elevations of sediment along a transect of Samosir reveal that minimum uplift rates were 4.9 cm/yr from 33.7 to 22.5 ka, but diminished to 0.7 cm/yr after 22.5ka. Thermo-mechanical models informed by these rates reveal that detumescence does not produce the uplift nor the uplift rates estimated for Samosir. However, models calculating the effect of volume change of the magma reservoir within a temperature-dependent viscoelastic host rock reveal that a single pulse of 475 km3 of magma produces a better fit to the uplift data than a constant flux. Reproducing the uplift rates require more sophisticated models. Motivation for resurgent uplift of the caldera floor is rebound of remnant magma as the system re-established magmastatic and isostatic equilibrium after the caldera collapse. Previous assertions that the caldera floor was apparently at 400m a.s.l or lower requires that uplift must have initiated between sometime between 33.7 ka and 74 ka at a minimum average uplift rate of 1.1 cm/ year. The change in uplift rate from pre-33.7 ka to immediately post-33.7 ka suggests a role for deep recharge augmenting rebound. Average minimum rates of resurgent uplift at Toba are at least an order of magnitude slower than net rates of "restlessness" at currently active calderas. This connotes a distinction between resurgence and “restlessness” controlled by different processes, scales of process, and controlling variables.